Implementing comprehensive geriatric assessment in an academic hematologic outpatient setting: experiences from medical doctors and patients - Hiltgen, Steven Pierre; Bischoff-Ferrari, Heike A.; Gagesch, Michael; Kaltenborn, Alexander; Manz, Markus G.; Rieger, Max J.; Schwotzer, Rahel; Stolz, Sebastian M.; Zenz, Thorsten; Rösler, Wiebke (Frontiers in Oncology, 2025)
IntroductionThe incidence of most cancers increases with age and cancer is a leading cause of morbidity and mortality in the older population. Older cancer patients frequently have additional co-morbidities and functional decline, which can substantially affect treatment outcomes. Major oncology societies recommend a screening for geriatric impairments in patients at risk (e.g. G8), followed by a comprehensive geriatric assessment (CGA). Nevertheless, CGA is often not established in routine care. We describe the implementation process of CGA in patients with hematological cancers at the University Hospital of Zurich. We evaluate its benefits, its perception by physicians and patients, and identify potential obstacles and solutions to allow integration into daily clinical practice.Materials and MethodsThis retrospective, single-center observational study was conducted at the University Hospital of Zurich. Patients aged ≥65 years with hematological malignancies who underwent CGA within the last 5 years were included. Patients were referred for CGA based on physicians’ choice. All data were extracted from electronic medical records and later analyzed. Perception of the CGA by patients and physicians was assessed by a questionnaire.Results46 patients who underwent CGA between April 2019 and July 2023 were included in this study. 89.1% showed at least one impaired domain in the CGA. For 98% of patients, one or more interventions were suggested. Low G8 scores were significantly associated with detected CGA-impairments (p<0.05). 70% of patients found the CGA and its resulting recommendations useful and reported benefiting from the process. 75% of the physicians rated the resulting CGA report as helpful for their clinical assessment.ConclusionOur data support the use of a CGA in older patients with hematological cancers based on positive feedback on its implementation, from both patients and treating physicians. Our results emphasize the need for a dedicated geriatric assessment in an older cancer population as it contributes to a more comprehensive medical evaluation and potentially improves overall care and quality of life for patients.